CHOLESTEATOMA- THE SILENT KILLER. - SUMITHA.R; NARAYAN, VIBINA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective-Cholesteatoma has been discussed in all International and National conferences periodically because it is an enigma. The treatment options keep on changing due to sustained recurrence even after perfect surgery. It is a silent killer and therefore is of utmost importance to diagnose and treat this condition early to reduce the mortality and morbidity. Method-In this study we discuss in detail about the etiopathogenesis and various modalities of treatment of Cholesteatoma with reference to modern surgical management. This study has been done in our hospital for a cross section of patients attending the outpatient department during the period January 2012 to Sep 2013 with evidence of cholesteatoma. Various aspects of the disease including age, socio economic status, clinical presentation, Per Op findingsÂ and complications were also analysed. Results-In this study of 30 patients with cholesteatomaÂ all of them underwent surgery â€“Modified Radical Mastoidectomy with exenteration of all accessible diseased air cells. The disease was common in middle aged females of lower socio economic class. The incidence of complication due to disease was 30percent [n=9]. The Post op follow up showed recurrence in only 20percent [n=6]. Conclusion-Cholesteatoma is one of the entities in ear which requires immediate attention to prevent devastating complications. In the present era with the advent of higher antibiotics and advanced surgical methods the incidence of complications has drastically come down and the disease is also managed more effectively with least morbidity. This study aims to be a comprehensive one to throw light on the dimension of this disease and its management. Keywords: Cholesteatoma, Mastoidectomy, Intracranial complications, Squamous epithelium, Endoscope.